Anticoagulant and disease-modifying therapy for atrial fibrillation and heart failure in certain Russian regions in 2023 - M. A. Druzhilov; O. Yu. Druzhilova; T. Yu. Kuznetsova; D. V. Gavrilov (Кардиоваскулярная терапия и профилактика)
Aim. Retrospective analysis of the prescription rate of anticoagulant and disease-modifying therapy (DMT) to patients with atrial fibrillation (AF) and heart failure (HF) in certain Russian regions as of December 31, 2023.Material and methods. A group of patients with AF and HF (n=7901, men 51,1%, mean age 72,4±11,3 years, mean CHA2DS2-VASc (congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, stroke, vascular disease, age 65 to 74 years, sex category) score 4,1±1,5) was formed based on data from the Webiomed predictive analytics platform and presented by depersonalized formalized data extracted using continuous sampling from electronic health records of patients aged ≥18 years in 22 Russian regions.Results. The anticoagulation prescription rate in the whole sample was 77,8%, while the proportion of direct oral anticoagulants was 72,9%. With CHA2DS2-VASc score ≥2 in men and ≥3 in women, anticoagulant therapy was prescribed in 77,9%. Renin-angiotensin-aldosterone system blockers were prescribed in 84,0% (valsartan+sacubitril — in 10,3%), β-blockers — in 80,2%, mineralocorticoid receptor antagonists — in 60,4%, sodium-glucose cotransporter 2 inhibitors — in 13,9%. In the subgroup of individuals with reduced and mildly reduced left ventricular ejection fraction, 4-agent DMT was received by 17,4%, 3-agent — by 42,6% of patients.Conclusion. Despite the positive changes in anticoagulant prescription rate and related proportion of direct oral anticoagulants for AF and HF in certain Russian regions in 2023 compared to a similar analysis for 2019 (62,5 vs 51,2%), it can still be considered inconsistent with current clinical guidelines. With a high prescription rate of renin-angiotensin-aldosterone system blockers, β-blockers and mineralocorticoid receptor antagonists in patients with AF and HF, there is still a low proportion of people receiving 4-agent DMT.